2014
DOI: 10.1371/journal.pone.0085187
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-A Polymorphisms and Colorectal Cancer Risk: A Meta-Analysis

Abstract: Background and ObjectivesTumor necrosis factor-alpha (TNF-a) was related to inflammation and involved in the development of colorectal cancer. Polymorphisms located in TNF-a promoter region, such as 308G/A and 238G/A, could affect the risk of various types of cancer by regulating TNF-a production. In this study, a meta-analysis was performed to investigate the association between common polymorphisms of TNF-a promoter region and colorectal cancer susceptibility.MethodsSearching of several databases was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
(42 reference statements)
2
29
0
Order By: Relevance
“…However, the small number of studies and subjects included makes it difficult to justify the usefulness of the polymorphism as a biomarker for colorectal cancer predisposition. The c.‐488G>A polymorphism, however, was found to be significantly associated with an increased colorectal cancer risk, based on the combined data from 14 studies involving 2837 cases and 3601 controls (AA versus GG: OR = 1.46, 95% CI = 1.07–1.97) . The heightened risk was consistent with the previous observation that the variant A allele of polymorphism can result in a two‐fold increase in TNF transcription by improving binding of transcription factor on the gene promoter .…”
Section: Genes Encoding Cytokinessupporting
confidence: 87%
See 1 more Smart Citation
“…However, the small number of studies and subjects included makes it difficult to justify the usefulness of the polymorphism as a biomarker for colorectal cancer predisposition. The c.‐488G>A polymorphism, however, was found to be significantly associated with an increased colorectal cancer risk, based on the combined data from 14 studies involving 2837 cases and 3601 controls (AA versus GG: OR = 1.46, 95% CI = 1.07–1.97) . The heightened risk was consistent with the previous observation that the variant A allele of polymorphism can result in a two‐fold increase in TNF transcription by improving binding of transcription factor on the gene promoter .…”
Section: Genes Encoding Cytokinessupporting
confidence: 87%
“…In particular, the c.‐418G>A (rs361525) and c.‐488G>A (rs1800629) polymorphisms (previously known as ‐238G>A and ‐308G>A) have received the most attention because their functional impact with respect to TNF transcription has been formally established. For the former polymorphism, a meta‐analysis based on four studies (535 cases and 922 controls) found no significant risk association with colorectal cancer . However, the small number of studies and subjects included makes it difficult to justify the usefulness of the polymorphism as a biomarker for colorectal cancer predisposition.…”
Section: Genes Encoding Cytokinesmentioning
confidence: 99%
“…However, routine anti‐TNF trials have not shown much clinical efficacy, as TNF plays an important role in host defense and it is uncertain to what extent therapy with anti‐TNF agents might be associated with an increase in serious infections and malignancies. In particular, blocking their traffic reveals a practical way to tackle the formidable problem . Our data indicated that paeonol not only reduced the production of proinflammatory cytokines but also disrupted the cellular responses to them.…”
Section: Discussionmentioning
confidence: 79%
“…Meta-analysis of Fan et al (2011) described no significant association of TNFα-308 polymorphism and colon cancer in any European ethnic population included in the meta-analysis. On the other side meta-analysis of Min et al (2014) found TNFα 308A moderately associated with an increased risk of colorectal cancer in Western populations, and TNFα 238A polymorphism not significantly associated with colorectal cancer risk. Any of the previously mentioned reports, except ours, did not include the population from Western Balkan countries.…”
Section: Discussionmentioning
confidence: 98%